1999
DOI: 10.1046/j.1365-2125.1999.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antiplatelet activity of microencapsulated aspirin 162.5 mg (Caspac XL), with enteric coated aspirin 75 mg and 150 mg in patients with atherosclerosis

Abstract: Aims A new formulation, low dose microencapsulated aspirin, permits slow absorption of aspirin and presystemic acetylation of platelet cyclo-oxygenase within the portal circulation, potentially avoiding deleterious effects on gastric and systemic prostaglandin synthesis. The objective of this study was to determine whether the administration of microencapsulated aspirin was as effective as enteric coated (EC) aspirin as an inhibitor of platelet function in patients with atherosclerosis. Methods One hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The present results suggest that the better platelet function profile of ER formulations of ASA in comparison with PF may be influenced by the role of SA and the relative lack of interference with prostacyclin synthesis. Moreover, our findings support the hypothesis put forward by Brown et al [25] that the anti‐aggregant effect of microencapsulated ASA is not entirely dependent on the inhibition of platelet thromboxane synthesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results suggest that the better platelet function profile of ER formulations of ASA in comparison with PF may be influenced by the role of SA and the relative lack of interference with prostacyclin synthesis. Moreover, our findings support the hypothesis put forward by Brown et al [25] that the anti‐aggregant effect of microencapsulated ASA is not entirely dependent on the inhibition of platelet thromboxane synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Brown et al [25] showed that the inhibition of platelet aggregation after the administration of a microencapsulated form of ASA (Caspac XL) was not entirely dependent on the inhibition of platelet thromboxane synthesis. This finding showed that an additional mechanism may be involved in the differences in pharmacokinetic profile between ER and PF ASA.…”
Section: Discussionmentioning
confidence: 99%